2000
DOI: 10.1046/j.1439-0442.2000.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Immunohistochemical Studies on Cetaceans Found Stranded on the Coast of Italy between 1990 and 1997

Abstract: Detailed histopathological and immunohistochemical studies were carried out on 24 cetaceans, 17 of which were striped dolphins (Stenella coeruleoalba), four bottlenose dolphins (Tursiops truncatus) and three Risso's dolphins (Grampus griseus), all found stranded on the Italian coast between 1990 and 1997. The most frequently detected lesions were chronic pneumonia (73.7% of the examined lungs), focal chronic pancreatitis (71.4%), non-purulent encephalitis (50%), chronic hepatitis (42.1%), and chronic focal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
6
29
0
Order By: Relevance
“…General descriptions of dolphin thoracic ultrasound exams have been published in marine mammal textbooks (Stone 1990, Brook et al 2001. However, there are currently no peer-reviewed publications on thoracic ultrasound techniques or findings in dolphins.A retrospective epidemiologic analysis of lung histopathology from the past 30 yr (1980 to 2010) of US Navy Marine Mammal Program data showed that the most common pulmonary pathology was pneumonia (Venn-Watson et al 2012), which is similar to findings of wild dolphin necropsies (Baker 1992, Di Guardo et al 1995, Cornaglia et al 2000, Bogomolni et al 2010. In both wild and managed dolphins, bacterial pneumonias have been reported often (Cusick & Bullock 1973, Sweeney & Ridgway 1975, Diamond et al 1979, Tangredi & Medway 1980, Howard et al 1983, Schulman et al 1997, Miller et al 1999, Dunn et al 2001, Makara et al 2007, St. Leger et al 2009), as well as fungal (Carroll et al 1968, Migaki et al 1978, Gales et al 1985, Joseph et al 1986, Schulman et al 1997, Jensen et al 1998, Reidarson et al 1998a,b, Miller et al 2002, Elad et al 2011), viral (Domingo et al.…”
mentioning
confidence: 68%
“…General descriptions of dolphin thoracic ultrasound exams have been published in marine mammal textbooks (Stone 1990, Brook et al 2001. However, there are currently no peer-reviewed publications on thoracic ultrasound techniques or findings in dolphins.A retrospective epidemiologic analysis of lung histopathology from the past 30 yr (1980 to 2010) of US Navy Marine Mammal Program data showed that the most common pulmonary pathology was pneumonia (Venn-Watson et al 2012), which is similar to findings of wild dolphin necropsies (Baker 1992, Di Guardo et al 1995, Cornaglia et al 2000, Bogomolni et al 2010. In both wild and managed dolphins, bacterial pneumonias have been reported often (Cusick & Bullock 1973, Sweeney & Ridgway 1975, Diamond et al 1979, Tangredi & Medway 1980, Howard et al 1983, Schulman et al 1997, Miller et al 1999, Dunn et al 2001, Makara et al 2007, St. Leger et al 2009), as well as fungal (Carroll et al 1968, Migaki et al 1978, Gales et al 1985, Joseph et al 1986, Schulman et al 1997, Jensen et al 1998, Reidarson et al 1998a,b, Miller et al 2002, Elad et al 2011), viral (Domingo et al.…”
mentioning
confidence: 68%
“…Parasitism, especially of the respiratory or gastrointestinal system, is relatively common in stranded cetaceans and has been documented in animals from the North Sea, eastern Pacific Ocean, and Atlantic Ocean (Baker 1992, Cornaglia et al 2000, Parsons & Jefferson 2000, Jauniaux et al 2002. Lungworm infections associated with stranding or mortality have been documented in harbor porpoises Phocoena phocoena, striped dolphins Stenella coeruleoalba, and finless porpoises Neophocaena phocaenoides (Cornaglia et al 2000, Parsons & Jefferson 2000, Siebert et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Lungworm infections associated with stranding or mortality have been documented in harbor porpoises Phocoena phocoena, striped dolphins Stenella coeruleoalba, and finless porpoises Neophocaena phocaenoides (Cornaglia et al 2000, Parsons & Jefferson 2000, Siebert et al 2001. Dailey (1985) suggested that lungworms could be a major mortality factor for cetacean populations.…”
Section: Introductionmentioning
confidence: 99%
“…In the whale reported here, the obstruction caused by the fishing artefact in the digestive tract must have resulted in the inability of this animal to feed. In addition, the bronchial fibrosis probably compromised normal breathing, as respiratory parasites are already known to have affected the health of cetaceans in the North Sea and Eastern Pacific and Atlantic Oceans (Baker, 1992;Cornaglia et al, 2000;Parsons & Jefferson, 2000;Fauquier et al, 2009). Summed to all that, a higher metabolic demand, which mammals present during pregnancy (Schillo, 2009), should have aggravated the pathological condition of the animal.…”
Section: Discussionmentioning
confidence: 99%